Hubungan Antara Waist To Height Ratio (WHtR) Dengan Heart Rate Recpvery (HRR) Pada Subyek Remaja Laki-laki - Rizqi Husni Mudzakkir; Agus Prastowo; Khusnul Muflikhah (JURNAL NUTRISIA, 2016)
Background: The prevalence of obesity and cardiovascular disease remains a national problem. Banyumas, Central Java, is one of the districts where the prevalence of obesity and the risk of cardiovascular disease are high. WHtR is an anthropometric index that can be a parameter for early detection of cardiovascular disease risks. HRR is a physiological indicator of the heart’s function that can be associated with cardiovascular disease in adolescence. Objective: To determine the association between WHtR and HRR in adolescent boys. Methods: This is an analytic observational study with cross sectional approach. Total research subjects were 128 adolescent boys were divided into two groups: normal WHtR (n = 64) and abnormal WHtR (n = 64). WHtR data was obtained from ratio of waist circumference and height. HRR data was measured after the Kasch Step Test. Association between WHtR and HRR was analyzed using the Chi -square test (α = 0.05, 95% CI). Results: Value of WHtR in adolescent boys had a range of 0.34 - 0.70 with a mean of 0.49 ± 0.08. Value of HRR in adolescent boys had a range of 1-58 bpm with a mean of 20.63 ± 13.42 bpm. Chi-square test’s result was p=0.000, show there was a statistically significant association (p <0.05) between WHtR and HRR with the prevalence ratio (PR) = 3. Conclusion: There is an association between WHtR and HRR in adolescent boys. Adolescent boys with abnormal WHtR have 3 times higher risk obtaining a low HRR value than adolescent boys with normal WHtR. Keywords: waist to height ratio, heart rate recovery, adolescent boys